The effects of thermal and ethanolic stress in industrial strains of Saccharomyces cerevisiae (Research, Society and Development, 2020)
Saccharomyces cerevisiae is exceptional microorganisms used in biotechnological processes, mainly in the ethanol production chain. Studies of the cellular responses of industrial yeasts under ethanolic and thermal stress in an association are still incipient. This study aimed to evaluate the action of thermal and ethanolic stress in industrial strains of Saccharomyces cerevisiae under different temperatures and concentrations of ethanol, to understand whether these factors influence ethanol production. For cytotoxicity and genotoxicity tests, yeasts were grown in 2% YPD medium incubated for 10 hours at 250 rpm. After growth, the samples were grown in sugarcane juice in concentrations of 5, 10 and 15% ethanol and incubated at 30 and 40 ºC. In Petri dishes containing the solid medium YPD 2% the yeasts were dripped and incubated for 72 hours the cytotoxic action was analyzed by cell growth and genotoxicity through the comet assay and ethanol production by gas chromatography. Cell growth occurred in all conditions, however, at 30 ºC there was inhibition in 10% (v v-1) of ethanol being potentiated in 15% (v v-1), at 40 ºC. The genotoxicity analysis showed an induction of DNA damage in yeasts, however, the FLE yeast was the one with the highest DNA damage index. The yeast Pedra-2 was more tolerant and produced more ethanol, showing to be a tolerant strain concerning the analyzed fermentative interferents.